Personality styles and self-harm in adolescents of the city of Arequipa - Gallegos-Santos, Marilia (2018)
The objective of this research was to determine the relationship between personality styles and self-injury. The sample was of 997 students between 13 and 18 years old (M=15.24 years), who attended between third and fifth of secondary school in public and private schools of the city of Arequipa. The research design was of the transversal, descriptive - correlational type. The Millon Adolescent Personality Inventory (MAPI), the Sub-Scale of Self-injury and Self-injury Thoughts (SIBTI), and a sociodemographic survey were used. The results indicated that there is a prevalence of 34.9% in relation to self-injurious thoughts, while 27.9% of those evaluated have self-harmed, with the average age of onset of self-injury being 12.61 years. The main triggers are negative mood (48.2%) and family problems (39.9%). Likewise, we found that sensitive personality styles (r = .293; p<.001), inhibited (r = .203; p<.001), violent (r = .149; p<.001) are those that more are associated with self-injurious behaviors. It is concluded that sensitive, inhibited and violent personality styles are linked to a higher prevalence of self-injury in adolescents in the city of Arequipa.